The effect of sulforaphane on perinatal hypoxic-ischemic brain injury in rats - Kapoor, S; Kala, D; Svoboda, J; Daněk, J; Faridová, A; Brnoliaková, Z; Mikulecká, A; Folbergrová, J; Otáhal, J (Physiological research, 2022)
Perinatal hypoxic-ischemic insult (HII) is one of the main devastating causes of morbidity and mortality in newborns. HII induces brain injury which evolves to neurological sequelae later in life. Hypothermia is the only therapeutic approach available capable of diminishing brain impairment after HII. Finding a novel therapeutic method to reduce the severity of brain injury and its consequences is critical in neonatology. The present paper aimed to evaluate the effect of sulforaphane (SFN) pre-treatment on glucose metabolism, neurodegeneration, and functional outcome at the acute, sub-acute, and sub-chronic time intervals in the experimental model of perinatal hypoxic-ischemic insult in rats. To estimate the effect of SFN on brain glucose uptake we have performed 18F-deoxyglucose (FDG) microCT/PET. The activity of FDG was determined in the hippocampus and sensorimotor cortex. Neurodegeneration was assessed by histological analysis of Nissl-stained brain sections. To investigate functional outcomes a battery of behavioral tests was employed. We have shown that although SFN possesses a protective effect on glucose uptake in the ischemic hippocampus 24 h and 1 week after HII, no effect has been observed in the motor cortex. We have further shown that the ischemic hippocampal formation tends to be thinner in HIE and SFN treatment tends to reverse this pattern. We have observed subtle chronic movement deficit after HII detected by ladder rung walking test with no protective effect of SFN. SFN should be thus considered as a potent neuroprotective drug with the capability to interfere with pathophysiological processes triggered by perinatal hypoxic-ischemic insult.
Keywords: Glucose; Animals, Newborn; Hypoxia-Ischemia, Brain; Brain; poranění mozku; Brain Injuries; Hypoxia; sulfoxidy; glukosa; Sulfoxides; mozková hypoxie a ischemie; novorozená zvířata; isothiokyanatany; krysa rodu Rattus; fluorodeoxyglukosa F18; Animals; Fluorodeoxyglucose F18; zvířata; Rats; Isothiocyanates; mozek; hypoxie